2019
DOI: 10.1145/3230678
|View full text |Cite
|
Sign up to set email alerts
|

Did We Just Travel to the Past? Building and Evaluating With Cultural Presence Different Modes of VR-Mediated Experiences in Virtual Archaeology

Abstract: Over the past years, Virtual Archaeology has introduced more experiential elements in virtual reconstructions, therefore going beyond the traditional visualization of 3D architectural models. In the case of dissemination, these experiences equate to a trip in time, in which users witness what the past was like and learn about it. However, due to a lack of explicit theoretical frameworks and/or systematic evaluation focusing on such experiential elements, it is uncertain whether the intended goals are achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Simulation video gaming: The use of virtual simulation to mock up or reconstruct real life experiences is something that has been used for many decades across multiple disciplines including Aerospace, TV and Film production, Retail, Architecture and Archaeology [63] [15] [62]. More recently virtual simulation has started to be applied in healthcare and education settings [36][10].…”
Section: Related Workmentioning
confidence: 99%
“…Simulation video gaming: The use of virtual simulation to mock up or reconstruct real life experiences is something that has been used for many decades across multiple disciplines including Aerospace, TV and Film production, Retail, Architecture and Archaeology [63] [15] [62]. More recently virtual simulation has started to be applied in healthcare and education settings [36][10].…”
Section: Related Workmentioning
confidence: 99%
“…Another research focused on IT to enhance the experience at historical sites can be found in [34], where virtual reality technology is used in tourism and archeology for virtual reconstructions that go beyond the traditional visualization of 3D architectural models. This is achieved by making these virtual environments feel like traveling back in time through responsive characters, enhanced interaction, and multisensory realism.…”
Section: New Solutions For Blockchain Based Cultural Heritage Preserv...mentioning
confidence: 99%
“…The aesthetics of the Ottoman Imperial heritage are displayed online through the digital virtual museum, and viewers can get a complete sensory experience as long as they use the equipment. For garment restoration, in recent years, interactive technology has introduced more virtual elements for digital restoration, so it goes beyond the traditional restoration of cultural relics [24]. Victor Kuzmichev et al [25][26][27] reconstructed and restored historical men's garments and riding skirts in the late Victorian era, which indicates that it is a feasible approach to restoring garments by using virtual reality.…”
Section: Introductionmentioning
confidence: 99%